The immunosuppressive agents rapamycin, cyclosporin A and tacrolimus increase lipolysis, inhibit lipid storage and alter expression of genes involved in lipid metabolism in human adipose tissue - Pereira, Maria João (2013)
Cyclosporin A (CsA), tacrolimus and rapamycin are immunosuppressive agents (IAs) associated with insulin resistance and dyslipidemia, although their molecular effects on lipid metabolism in adipose tissue are unknown. We explored IAs effects on lipolysis, lipid storage and expression of genes involved on lipid metabolism in isolated human adipocytes and/or adipose tissue obtained via subcutaneous and omental fat biopsies. CsA, tacrolimus and rapamycin increased isoproterenol-stimulated lipolysis and inhibited lipid storage by 20–35% and enhanced isoproterenol-stimulated hormone-sensitive lipase Ser552 phosphorylation. Rapamycin also increased basal lipolysis ( 20%) and impaired insulin’s antilipolytic effect. Rapamycin, down-regulated the gene expression of perilipin, sterol regulatory element-binding protein 1 (SREBP1) and lipin 1, while tacrolimus down-regulated CD36 and aP2 gene expression. All three IAs increased IL-6 gene expression and secretion, but not expression and secretion of TNF-a or adiponectin. These findings suggest that CsA, tacrolimus and rapamycin enhance lipolysis, inhibit lipid storage and expression of lipogenic genes in adipose tissue, which may contribute to the development of dyslipidemia and insulin resistance associated with immunosuppressive therapy.